2011
DOI: 10.1097/acm.0b013e3181ff92cf
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Medical Education in Substance Abuse: A Review of the Quality of the Literature

Abstract: Purpose To prepare to develop a medical school curriculum on substance abuse disorders (SAD), the authors conducted a review of the quality of the sparse published literature. Method The authors searched MEDLINE (1950–December 2008), Web of Science, PsycINFO, and PubMed to identify all studies of SAD interventions targeted toward undergraduate medical students. Of the 1,084 studies identified initially, 31 reported sufficient data to allow the authors to evaluate quality using Medical Education Research Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 36 publications
0
50
0
Order By: Relevance
“…For the few instances of low interrater reliability, raw agreement was usually good; we return to this point in the Discussion. Four other studies [24][25][26][27] reported interrater reliabilities for overall MERSQI scores ranging from 0.68 to 0.89.…”
Section: Selection Of Comparison Groupmentioning
confidence: 96%
“…For the few instances of low interrater reliability, raw agreement was usually good; we return to this point in the Discussion. Four other studies [24][25][26][27] reported interrater reliabilities for overall MERSQI scores ranging from 0.68 to 0.89.…”
Section: Selection Of Comparison Groupmentioning
confidence: 96%
“…9 More recently, systematic reviews of medical education in topic areas unrelated to palliative care that utilized MERSQI have reported mean scores ranging from 9.0 to 11.4. [59][60][61][62][63][64][65][66] Overall, this suggests that palliative care education studies are of similar methodological quality to other medical education studies.…”
Section: Study Qualitymentioning
confidence: 96%
“…Approaches used to teach about SUDs during the undergraduate years are varied but literature suggests that active and experiential modalities are more effective for changing knowledge and attitudes (15). This is consistent with the heavy emphasis on patient interaction and skills development in this course.…”
Section: Discussionmentioning
confidence: 67%